Toxic metal ions contamination in the groundwater, Kingdom of Saudi Arabia. Issue 1 (1st January 2020) - Ali, Imran; Hasan, Mohd Abul; Alharbi, Omar M. L.
Abstract : The Kingdom of Saudi Arabia (KSA) is one of the rising countries in the Gulf region but always scared of water; being present in the arid desert. Among some water resources groundwater is one of the most significant ones in this country but unfortunately is being contaminated by the toxic metal ions. The present article describes the status of groundwater contamination by toxic metal ions. The meal ions analysed in the groundwater of KSA are Al, Cr, As, Cd, Ba, Co, Cu, Fe, Li, Hg, Mn, Ni, Se, Pb, V and Zn. This article describes the different groundwater resources in KSA, toxicities of the metal ions, metal ions contamination in the groundwater and sources of metal ions pollution. Besides, efforts are made to discuss the future challenges and the remediation measures; needed to protect the groundwater resources. This article will be important to the academicians, researchers, industry persons and the regulatory authorities.